Respuesta :

Answer:

y = 8400000

Step-by-step explanation:

5y - (2x10^6) = 4 x 10^7

First you evaluate the exponent:

5y - (2 x 1000000) = 4 x 10^7

Next, you multiply the numbers,

5y - (2000000) - 4 x 10^7

Multiply:

5y - 2000000 = 4 x 10^7

Evaluate the exponent again:

5y - 2000000 = 4 x 10000000

Multiply:

5y - 2000000 = 40000000

Add 2000000 to both sides of the equation:

5y - 2000000 + 2000000 = 40000000 + 2000000

Simplify:

5y = 42000000

Divide both sides of the equation by 5:

5y/5 = 42000000/5

Cancel out the terms that are in both the numerator and denominator then divide the numbers:

y = 8400000